Experimental evaluation of the performance of a domestic water heating system under Baghdad climate conditions - H. Attia, Osam; T. Al- Musawi, Sanaa; A. Mousa, Naseer; A. Mahmood, Hussein; Adam, Nor Mariah (Eastern-European Journal of Enterprise Technologies, 2022)
The aim of the current study is to evaluate the performance of a domestic water heating system for residential areas in Baghdad climatic conditions for substituting electric water heaters with solar-powered water heaters using solar collectors. Many countries, such as Iraq, are sluggish with electric power issues while receiving very high solar insolation. Solar energy is a clean, non-depleting and low-cost source that can be used especially in residential areas, which forms a great percentage of energy consumption by replacing electric water heating with solar water heating to reduce electricity usage. Therefore, six flat plate solar collectors with an absorbing area of 1.92×0.85 m with one 4 mm thick glass cover are utilized for experimental investigation under the Baghdad climatic conditions. The collector was tested under steady-state settings, which assumed that sunlight intensity, ambient temperature, and inlet-outdoor temperature difference in each collector in the system were constant throughout the operation. According to the experimental results, during the test months of November, December, January, and February, the time-weighted experimental daily average collector array efficiency is found in the range of 40 % to 60 %. Furthermore, the greater energy gain and performance of the solar collector array attain a peak value at solar noon. Additionally, a solar collector with flat plates can easily achieve relatively high water temperature levels of 70 °C in the winter season. In addition, using a solar domestic hot water system as a water heater in Baghdad climatic conditions by substituting electric water heaters is useful for saving power consumption